2014
DOI: 10.1007/s13277-014-1674-x
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic value of serum human kallikrein-related peptidases 11 in non-small cell lung cancer

Abstract: The aim of this study was to explore the diagnostic and prognostic value of serum human kallikrein-related peptidases 11 (KLK11) level in non-small cell lung cancer (NSCLC). Serum specimens from 138 patients with NSCLC and 40 healthy controls were collected. The concentration of KLK11 was measured by enzyme-linked immunosorbent assay (ELISA). The concentration of KLK11 in NSCLC was significantly higher compared to that in the controls (P < 0.01). The serum KLK11 levels decreased with stage, presence of lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The concentration of tissue proteases, which facilitate cancer cell invasion and metastasis, has been shown to increase in the blood of cancer patients; [1,2] the concentration of protease inhibitors also increases. [3] Beside the diagnostic value of protease concentrations, their activity can potentially influence molecules and cells circulating in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of tissue proteases, which facilitate cancer cell invasion and metastasis, has been shown to increase in the blood of cancer patients; [1,2] the concentration of protease inhibitors also increases. [3] Beside the diagnostic value of protease concentrations, their activity can potentially influence molecules and cells circulating in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…While in the LUAD-favorable gene set, genes that were significantly associated with LUAD survival included OR7E47P, MS4A2, RAB44, BMP5, ARHGEF6, KLK11and etc. Among them, KLK11 was found to be a diagnostic and prognostic indicator of NSCLC 31 . This just more confirms the possibility that the LUAD-unfavorable gene set and LUADunfavorable gene set can be used as a prognostic model for LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients with NSCLC had lower levels of KLK5, KLK7, KLK8, KLK10, and KLK12, and higher levels of KLK11, KLK13, and KLK14 compared to controls and proposed a multiparametric panel of kallikrein markers for the diagnosis of NSCLC with relatively good accuracy [ 7 ]. Similarly, Xu et al [ 5 ] evaluated the diagnostic and prognostic value of serum human kallikrein–related peptidases 11 level in NSCLC. They collected serum specimens from 138 patients with NSCLC and 40 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…They collected serum specimens from 138 patients with NSCLC and 40 healthy controls. They observed that serum human kallikrein–related peptidases 11 levels were significantly higher in NSCLC compared to that in the controls and NSCLC patients with serum high human kallikrein–related peptidases 11 had a longer overall survival and progression-free survival than those with low human kallikrein–related peptidases 11 and concluded that serum human kallikrein–related peptidases 11 might be a useful diagnostic and prognostic test for NSCLC patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation